Fantasia e utopia: a libertação em Herbert Marcuse - Matias, Ciro Augusto Mota (2018)
This work seeks to focus on the relevance of Marcusean conception of utopia and the possibility of political liberation from fantasy in the domain of generating values that challenge the prevalence and domination of the principle of repressive reality, in such a way that the critical theory of affluent and of technological rationality, a critical analysis of psychoanalysis and an aesthetic theory point to the possibility of political emancipation. Despite the achievements of affluent societies, accumulation of knowledge and technical development, quantitative progress still does not necessarily result in qualitative progress, the maintenance forces of the stablishment suffocate or absorb alternatives to overcoming the unequal and oppressive order of repressive society. The language expressed by the creative source of fantasy, art, can open loopholes for the qualitative transformations in established society, which, based on one-dimensional thinking, aims and has perpetuated the mechanisms and instruments of domination and exploitation, so that individuals introjecting the needs and aspirations of the repressive society, reinforcing the administration of human life and its gratifications by the aims and ends of the destructive logic of technological rationality under the dominion of capital, life mediated by exchange value. The point, then, is to understand how individuals who perceive themselves free and happy can aim for liberation; how conformist subjectivity is constructed and which vehicles are to overcome the alienated consciousness; as men and women forged in the values of bourgeois competitiveness can awaken to solidarity as a human value. Liberation is a process that demands the assumption of the material achievements of affluent society, but without awareness of the need to liberate destructive progress time persists in the historical continuum of domination. The aesthetic dimension can not transform reality, but it can generate awareness and transform sensual experience into men and women, who bearers of new needs and emancipated values, can forge a new society. Only political practice can accomplish the promises announced in the aesthetic dimension, in an open historical horizon, the still unfulfilled, authentic utopian force, fantasy and utopia invite to the Great Refusal.